2008
DOI: 10.1097/mlg.0b013e31816c7bc9
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Agent Microporous Polysaccharide Hemospheres (MPH) Does Not Affect Healing or Intact Sinus Mucosa

Abstract: Absorbable hemostatic materials have starkly different effects on mucosal healing. Unlike other agents, MPH is rapidly cleared and has no negative effects on healing or intact sinus mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 14 publications
0
47
1
3
Order By: Relevance
“…MPH was found to be associated less with mucosal cilia loss, inflammation and fibrosis in a study comparing MPH and floseal following surgical intervention to the maxillary sinus in rabbits by Antisdel et al (1). In our study, no difference in neuronal degeneration between ORC and MPH was detected.…”
Section: Mph (Microporous Polysaccharide Hemospheres)mentioning
confidence: 40%
“…MPH was found to be associated less with mucosal cilia loss, inflammation and fibrosis in a study comparing MPH and floseal following surgical intervention to the maxillary sinus in rabbits by Antisdel et al (1). In our study, no difference in neuronal degeneration between ORC and MPH was detected.…”
Section: Mph (Microporous Polysaccharide Hemospheres)mentioning
confidence: 40%
“…The rapid absorption kinetics and composition of MPH also explain why this material does not interfere with the mucosal regeneration and wound healing. 4 The 'no treatment' control used in this study permits comparison to what the patient would otherwise have experienced as 'normal recovery' from surgery. A noteworthy fi nding was that the use of MPH did not signifi cantly alter the pain, obstruction, or discharge that patients experienced following ESS.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, MPH does not impact healing or intact sinus mucosa in animals. 4 Acting as a 'molecular sieve' by osmotically extracting fl uids from blood, MPH particles concentrate platelets and other elements promoting the formation of a fi brin clot. Unlike most agents which are derived from animal products, MPH is made from purifi ed potato starch and is hypoallergenic with no inherent risk of disease transmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 Gelatin thrombin matrix: It stops bleeding on an average of 2 minutes. 26 Some studies reported its adverse effect, 27,28,29 but one study evaluated its efficiency without complications. 30 Others: Microporous polysaccharide hemispheres, 31,32 oxidised methylcellulose, 33 fibrin glue, 34 microfibrillar collagen 35 and gelatin sponges 36 can be used to control intraoperative bleeding.…”
Section: Surgical Considerationsmentioning
confidence: 99%